Endeavour. The complete eighth season [videorecording (DVD)] - Evans, Shaun, 1980-; Evans, Shaun, 1980-; Allam, Roger; Lesser, Anton; Bradshaw, James, 1976-; Rigby, Sean; Richards, Dakota Blue, 1994-; Dexter, Colin (PBS, 2022)
1971 has barely just begun and CID is still reeling from the events of the past year. Any hope of remaining on light duties has vanished and the team find themselves right back in the thick of it.